1992
DOI: 10.1111/j.1365-3040.1992.tb01456.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoinhibitory responses of the epiphytic bromeliad Guzmania monostachia during the dry season in Trinidad maintain photochemical integrity under adverse conditions

Abstract: The C3–CAM epiphytic bromeliad Guzmania monostachia var. monostachia may be exposed to high incident photosynthetically active radiation (PAR) during the dry season in Trinidad, and resultant variations in photochemical efficiency have been investigated for ‘exposed’ (receiving ∼100% incident PAR), ‘semi‐exposed’ (∼60% PAR) and shaded populations under natural conditions. The more succulent leaves of the plants growing fully exposed within the canopy had higher overall CAM activity (measured as ΔH+, the dawn‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 28 publications
2
31
0
3
Order By: Relevance
“…Some authors have postulated that nocturnal accumulation of organic acids in CAM plants may alleviate photoinhibition Haag-Kerver et al 1992Maxwell et al 1992. The light response curves presented here showed a clear differentiation between phase III and phase IV of CAM in C. hilariana, when higher 1-qP and qN were observed in this latter phase.…”
Section: Diurnal Course Of Chlorophyll a Fluorescence In The Plants Osupporting
confidence: 53%
“…Some authors have postulated that nocturnal accumulation of organic acids in CAM plants may alleviate photoinhibition Haag-Kerver et al 1992Maxwell et al 1992. The light response curves presented here showed a clear differentiation between phase III and phase IV of CAM in C. hilariana, when higher 1-qP and qN were observed in this latter phase.…”
Section: Diurnal Course Of Chlorophyll a Fluorescence In The Plants Osupporting
confidence: 53%
“…It was also reported that Guzmania monostachia damaged by high light intensities had increased LCPs (Maxwell et al, 1992), indicating that J. dubia was also injured by high light intensities under 0% shade. Both A n and maximum A n varied significantly (p < 0.05) among the light intensity treatments.…”
Section: Resultsmentioning
confidence: 85%
“…Among the bromeliads, the best recognized facultative CAM species is Guzmania monostachia (Medina et al, 1977;Griffiths and Smith, 1983;Maxwell et al, 1992). This epiphytic tank bromeliad is widespread throughout the middle to upper canopy in neotropical forests and shows a high capacity of acclimation in response to variations in the natural environment (Maxwell et al, 1994).…”
Section: Introductionmentioning
confidence: 99%